2012
DOI: 10.1021/ct300085z
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM-Based Fitting of Atomic Polarizabilities for Use in Condensed-Phase Biomolecular Simulation

Abstract: Accounting for electronic polarization effects in biomolecular simulation (by using a polarizable force field) can increase the accuracy of simulation results. However, the use of gas-phase estimates of atomic polarizabilities αi usually leads to overpolarization in condensed-phase systems. In the current work, a combined QM/MM approach has been employed to obtain condensed-phase estimates of atomic polarizabilities for water and methanol (QM) solutes in the presence of (MM) solvents of different polarity. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 87 publications
(169 reference statements)
4
51
0
Order By: Relevance
“…Combined with the electric fields at the atoms and assuming linear response, polarizabilities can be calculated. It was shown that the values for the atomic polarizabilities obtained are similar to those previously reported based on empirical optimization, and they could be directly used to guide calibration of a methanol solvent model (CPC) …”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Combined with the electric fields at the atoms and assuming linear response, polarizabilities can be calculated. It was shown that the values for the atomic polarizabilities obtained are similar to those previously reported based on empirical optimization, and they could be directly used to guide calibration of a methanol solvent model (CPC) …”
Section: Introductionsupporting
confidence: 71%
“…One of the challenges in calibrating polarizable force fields is assigning appropriate values to the atomic polarizabilities . In the current work, we make profit from a recently proposed QM/MM approach to estimate atomic polarizabilities that are suited for use in condensed‐phase environment . In this approach, solvent configurations around a solute are sampled through MD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Then one could use that understanding to develop a proper parameterization scheme and, since the polarizability in condensed phase (even in water pentamer) can significantly differ from that in the gas phase, 128131 use QM/MM calculations to fit anisotropic atomic polarizabilities in a self-consistent fashion. 132,133 …”
Section: Discussionmentioning
confidence: 99%
“…This method is based on linear response theory and was proposed by Karamertzanis et al 73 . who showed that under the approximation of linear electronic response, the sum of electrostatic and polarization interactions of a molecule with an external electric field is equal to the electrostatic interaction of a half-polarized molecule with the same field 74 , 75 . This means that atomic multipoles in a non-polarizable force field should be based on a (distributed) multipole expansion of the average of the vacuum and solvated electron densities.…”
Section: Methodsmentioning
confidence: 99%